Heavy mesons decays in the light-front - De Melo, J. P.B.C. [UNESP]; Frederico, T. (AIP Publishing, 2010)
The light-front approach is applied to calculate electromagnetic form factors of pseudoscalar mesons (ie., pion, kaon and D mesons) and semileptonic transition form factors of the heavy ones. The results are compared with the new experimental data from CLEO and lattice calculations. © 2010 American Institute of Physics.
Keywords: Constituent Quarks; Heavy Mesons; Light-Front; QCD